2021
DOI: 10.3390/ijms22052549
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Applications of Hydrogen in Chronic Inflammatory Diseases: Possible Inhibiting Role on Mitochondrial Stress

Abstract: Mitochondria are the largest source of reactive oxygen species (ROS) and are intracellular organelles that produce large amounts of the most potent hydroxyl radical (·OH). Molecular hydrogen (H2) can selectively eliminate ·OH generated inside of the mitochondria. Inflammation is induced by the release of proinflammatory cytokines produced by macrophages and neutrophils. However, an uncontrolled or exaggerated response often occurs, resulting in severe inflammation that can lead to acute or chronic inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 59 publications
0
40
0
1
Order By: Relevance
“…Zhou et al, who examined the radioprotective effects of H 2 on a rat skin damage model, showed that H 2 significantly reduced MDA and IL-6 levels in the damaged skin [ 52 ]. In a recent review, we reported that •OH generated in mitochondria induces oxidative stress in mitochondrial DNA (mtDNA), and that oxidized mtDNA triggers a cascade of inflammatory cytokine release from nucleotide-binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) to IL-1 and IL-18 [ 57 ]. The mechanism of H 2 -induced amelioration of chronic inflammatory diseases may involve the scavenging of •OH generated in mitochondria [ 57 ].…”
Section: Mechanism Of the Radioprotective Effects Of Hmentioning
confidence: 99%
“…Zhou et al, who examined the radioprotective effects of H 2 on a rat skin damage model, showed that H 2 significantly reduced MDA and IL-6 levels in the damaged skin [ 52 ]. In a recent review, we reported that •OH generated in mitochondria induces oxidative stress in mitochondrial DNA (mtDNA), and that oxidized mtDNA triggers a cascade of inflammatory cytokine release from nucleotide-binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) to IL-1 and IL-18 [ 57 ]. The mechanism of H 2 -induced amelioration of chronic inflammatory diseases may involve the scavenging of •OH generated in mitochondria [ 57 ].…”
Section: Mechanism Of the Radioprotective Effects Of Hmentioning
confidence: 99%
“…Humans have an extensive immune system by which specialized cells can combat pathogens that enter the body. In particular, inflammation is the process by which macrophages and neutrophils release proinflammatory cytokines, such as interleukin (IL)-1β and IL-18, in direct response to this stimulus [1,[5][6][7]. Such a signal is often transient in order to trigger a quick response for the body to fight against these pathogens.…”
Section: Chronic Inflammation the Root Cause Of Mibyou And "Silent Killers"mentioning
confidence: 99%
“…Of particular interest is the nucleotide-binding domain leucine-rich repeat and pyrin domain containing receptor 3 (NLRP3) inflammasome, which is implicated in the development of many known inflammatory diseases and commonly studied in order to inhibit the progression of chronic inflammation [8][9][10]. While the specific mechanism by which NLRP3 inflammasomes are activated is yet to be discovered, it is known that ROS play a key role in the activation step of these innate immune system receptors [1]. More specifically, ROS can oxidize mitochondrial DNA (mtDNA) that bind to NLRP3 inflammasomes in order to activate them [10].…”
Section: Oxidative Stress In Chronic Inflammationmentioning
confidence: 99%
See 2 more Smart Citations